Clinical and Biological Study of Rheumatoid Arthritis Influence on Salivary Biomarkers in Patients with Periodontal Disease* - Boatca Madalin; Hurjui Loredana; Rudnic Ioana; Nicolaiciuc Ovidiu; Martu Silvia (Balkan Stomatological Society, 2015)
Aim: The purpose was to identify if rheumatoid arthritis (RA) influenced levels of salivary biomarkers of periodontal disease.